Biomechanical Comparison of Four- versus Six-Strand Transosseous Suture Repair for Patellar Tendon Rupture - Zhang, Tina; Wahl, Alexander; Schneider, Matheus; Xu, Dali; Hahn, Alexander; Meredith, Sean J.; Packer, Jonathan D.; Leong, Natalie L.; Zhang, Li-Qun; Henn, R. Frank, III; Jauregui, Julio J. (The Journal of Knee Surgery, 2023)
Background Surgical repair is indicated for patellar tendon ruptures that result in loss of knee extensor mechanism function. However, biomechanical studies report conflicting results when comparing transosseous suture versus suture anchor repair techniques. This discrepancy may be due to inconsistencies in experimental design as these studies use various numbers of suture strands. Therefore, the main objective of this study is to compare the ultimate load of four- versus six-strand transosseous suture repair. Secondary objectives are to compare gap formation after cyclical loading and mode of failure.Methods Six pairs of fresh-frozen cadaveric specimen were randomly allocated to either four- or six-strand transosseous suture repair. Specimen underwent preconditioning cyclical loading and then load to failure.Results The six-strand repair had a significantly higher maximum load to failure compared with the four-strand repair (mean difference = 319.3 N [57.9%], p = 0.03). There was no significant difference in gap length after cyclical loading or at max load. There were no significant differences in mode of failure.Conclusion Utilizing a six-stand transosseous patella tendon repair construct with one additional suture increases overall construct strength by over 50% compared with a four-strand construct.
Keywords: biomechanics; patellar tendon rupture; transosseous fixation; patellar tendon repair